2021
DOI: 10.1002/path.5659
|View full text |Cite
|
Sign up to set email alerts
|

The EMT transcription factor ZEB1 blocks osteoblastic differentiation in bone development and osteosarcoma

Abstract: Osteosarcoma is an often‐fatal mesenchyme‐derived malignancy in children and young adults. Overexpression of EMT‐transcription factors (EMT‐TFs) has been associated with poor clinical outcome. Here, we demonstrated that the EMT‐TF ZEB1 is able to block osteoblastic differentiation in normal bone development as well as in osteosarcoma cells. Consequently, overexpression of ZEB1 in osteosarcoma characterizes poorly differentiated, highly metastatic subgroups and its depletion induces differentiation of osteosarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Kahlert et al proved that a mesenchymal transition process involved in the onset and progression of sarcomas. More evidence showed OS cells undergo the EMT process that associate with their metastatic ability [27][28][29]. Consistently, we found NPR3 overexpression led to increase the expression level of E-cadherin and decrease the expression level of EMT-activating proteins, such as Ncadherin, vimentin, snail, twist1, ZEB1 which increased migratory and invasive potential [30].…”
Section: Discussionsupporting
confidence: 84%
“…Kahlert et al proved that a mesenchymal transition process involved in the onset and progression of sarcomas. More evidence showed OS cells undergo the EMT process that associate with their metastatic ability [27][28][29]. Consistently, we found NPR3 overexpression led to increase the expression level of E-cadherin and decrease the expression level of EMT-activating proteins, such as Ncadherin, vimentin, snail, twist1, ZEB1 which increased migratory and invasive potential [30].…”
Section: Discussionsupporting
confidence: 84%
“…In non‐small‐cell lung cancer (NSCLC), activation of the AXL receptor tyrosine kinase in the course of EMT provides resistance to EGFR and PI3K inhibition, dependent on sustained KRAS activity (Singh et al , 2009 ; Sequist et al , 2011 ; Zhang et al , 2012 ; Byers et al , 2013 ; Tulchinsky et al , 2019 ). Furthermore, ZEB1 downregulation through HDAC class I inhibition or DNA demethylation resensitizes pancreatic cancer and osteosarcoma cells to chemotherapy (Meidhof et al , 2015 ; Ruh et al , 2021 ). Docetaxel‐resistance of lung adenocarcinoma cells and paclitaxel‐resistance of ovarian cancer cells can be reverted by blocking ZEB1 expression, providing increased survival of lung metastasis‐bearing mice upon treatment (Ren et al , 2013 ; Sakata et al , 2017 ).…”
Section: Non‐classical Emt Featuresmentioning
confidence: 99%
“…Reactivating expression of silenced genes has a similar effect in osteosarcoma. Demethylation of the imprinted DLK‐DIO3 locus by 5‐Azacitidine reactivates expression of ZEB1‐silencing miRNAs, induces osteogenic and adipogenic differentiation, and sensitizes to doxorubicin treatment (Ruh et al , 2021 ). The idea of transdifferentiation was nicely demonstrated by Ishay‐Ronen et al , showing that EMT‐derived breast cancer cells can be differentiated into post‐mitotic functional adipocytes by rosiglitazone in vivo , resulting in reduced metastasis (Ishay‐Ronen et al , 2019 ).…”
Section: Therapeutic Options To Target Emtmentioning
confidence: 99%
“…Treatment of osteosarcoma cells with decitabine was found to induce ERα expression, decrease proliferation and metastasis-associated markers, and cause osteoblast differentiation ( Supplementary Table S1 ) ( Osuna et al, 2019 ). Ruh et al (2021) recently demonstrated that Decitabine can induce the demethylation of imprinted DLK-DIO3 locus resulting in the downregulation of ZEB1 via microRNAs (miRNAs) expression in osteosarcoma cells. The reduction of ZEB1 expression levels induced an adipogenic and osteogenic differentiation in the cells, as well as improved the response to doxorubicin.…”
Section: Differentiation Therapymentioning
confidence: 99%